High-Precision Offshore Wind Energy Assessment Using SAR Satellite Data: A Case Study of Zhuanghe Offshore Waters - Yuan, Ling; Long, Haichuan; Ruan, Xia; Yang, Fengzhi; Li, Jianke; Chen, Peng (Sustainable Marine Structures, 2026)
With growing global demand for clean energy, offshore wind resource assessment is crucial. This study comprehensively utilizes multi-source Synthetic Aperture Radar (SAR) satellite data, including European Sentinel-1 and Chinese Gaofen-3 satellites, along with in-situ wind mast measurements, to systematically assess the wind energy resources in the offshore area of Zhuanghe, Liaoning Province, China, from 2017 to 2022. Sea surface wind fields were retrieved through data preprocessing, polarization conversion, geophysical model inversion, and multi-source data fusion. By coupling a vertical extrapolation model that accounts for sea state effects, the 10‑m wind speeds were extrapolated to turbine hub heights of 40 m, 80 m, and 100 m, enabling the calculation of key wind energy parameters such as wind speed and wind power density. Results indicate that at 100 m height, the annual average wind speed is 6.40 m·s−1 and the annual average wind power density is 312.8 W·m−2, corresponding to wind class 2. Wind speeds are higher in spring and winter and lower in summer and autumn, with prevailing northerly winds. Compared with ERA5 reanalysis data, SAR data offer advantages including high spatial resolution, rich historical records, and superior local accuracy, making them suitable for detailed offshore wind resource assessment. This research fills the gap in high‑precision wind energy evaluation under complex meteorological and data‑scarce conditions in the region, provides reliable data support for local offshore wind farm planning and development, and offers transferable experience for the application of SAR technology in similar coastal areas in China. ER